RESEARCH OF THE FACTOR STRUCTURE OF THE MODEL OF WORLD VIEW SETTINGS AT A YOUNG AGE - Kononenko, Oksana; Kononenko, Anatoliy; Stynska, Viktoriia; Kachmar, Oleksandra; Prokopiv, Liubov; Katolyk, Halyna; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose of the empirical study is to construct the factor structure of the model of world view settings and to establish peculiar features of the formation of world view settings in the youth period. World view settings are important elements in shaping the formation of the educational process. Research methods: test methods with standardized questionnaires and factor analysis. The structure of the model of world view systems was determined by factor analysis. The most significant interrelations of world view settings and the studied variables were established at the level (p≤.01; p≤.05). A model of the world view settings of personality attitudes was developed, combining five factors (72.43%): F 1 “The Meaning of Life”; F 2 “Anxiety”; F 3 “Aggressiveness”; F 4 “Spiritual values / material values” and F 5 “Friendship”. The data obtained give an objective The purpose of the empirical study is to construct the factor structure of the model of world view settings and to establish peculiar features of the formation of world view settings in the youth period. World view settings are important elements in shaping the formation of the educational process. Research methods: test methods with standardized questionnaires and factor analysis. The structure of the model of world view systems was determined by factor analysis. The most significant interrelations of world view settings and the studied variables were established at the level (p≤.01; p≤.05). A model of the world view settings of personality attitudes was developed, combining five factors (72.43%): F 1 “The Meaning of Life”; F 2 “Anxiety”; F 3 “Aggressiveness”; F 4 “Spiritual values / material values” and F 5 “Friendship”. The data obtained give an objective